1991
DOI: 10.1021/es00024a010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tetrachloromethane sorption to an alkylammonium-clay and an alkyldiammonium-clay

Abstract: The interlamellar space of Wyoming bentonite (clay) was modified by exchanging either decyltrimethylammonium (DTMA) or decyltrimethyldiammonium (DTMDA) cations for inorganic ions, and tetrachloromethane sorption to the resulting two organoclays from water was studied at 10, 20, and 35 °C. Only one end of the 10-carbon alkyl chain of the DTMA cation is attached to the silica surface of the clay mineral, and tetrachloromethane sorption of DTMA-clay is characterized by isotherm linearity, noncompetitive sorption,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(35 citation statements)
references
References 22 publications
1
32
1
Order By: Relevance
“…Additionally, the sorptive capacity of the two organoclays demonstrates that the uptake of nonpolar benzene by HDTMA clay is linear and relatively weak compared to the nonlinear, strong sorptive uptake by the BTEA clay. While the sorption of benzene in this study was shown to decrease as the total organic carbon content was increased, previous research has determined that the sorption of carbon tetrachloride on BTEA clay increased as the total organic carbon content of the clay increased (14). Similarly, batch sorption tests with the hydrophobic herbicide norflurazon on BTEA clay also demonstrated that the degree of sorption increased as the total organic cation content increased; however, sorption of norflurazon to BTMA clay increased as the organic carbon exchanged was increased from 25 to 63% of the clay's CEC, but the sorption of norflurazon at 100% CEC was lower than at 63% CEC (30).…”
Section: Figcontrasting
confidence: 62%
“…Additionally, the sorptive capacity of the two organoclays demonstrates that the uptake of nonpolar benzene by HDTMA clay is linear and relatively weak compared to the nonlinear, strong sorptive uptake by the BTEA clay. While the sorption of benzene in this study was shown to decrease as the total organic carbon content was increased, previous research has determined that the sorption of carbon tetrachloride on BTEA clay increased as the total organic carbon content of the clay increased (14). Similarly, batch sorption tests with the hydrophobic herbicide norflurazon on BTEA clay also demonstrated that the degree of sorption increased as the total organic cation content increased; however, sorption of norflurazon to BTMA clay increased as the organic carbon exchanged was increased from 25 to 63% of the clay's CEC, but the sorption of norflurazon at 100% CEC was lower than at 63% CEC (30).…”
Section: Figcontrasting
confidence: 62%
“…Since the discovery about their unique adsorption capacity in the 1950s, modified bentonites have been a subject of a number of studies as adsorbents for the removal of pollutants from water. For the removal of organic pollutants, bentonites are often modified by quaternary ammonium cations [5][6][7][8][9]. In aqueous solution large quaternary ammonium organic cations readily replace the inorganic cations in the intermellar space of montmorillonites by ion exchange, and the bentonites are said to be intercalated.…”
Section: Introductionmentioning
confidence: 99%
“…When organic cations (cationic surfactants) of the form (CH 3 ) 3 NR + , where R is an alkyl hydrocarbon, occupy the exchange sites of bentonite clay, the surface properties transform from hydrophilic to hydrophobic. Recent studies have shown that the molecular structure of cationic surfactants used to modify clay affects the mechanism of NOC sorption [1][2][3][4]. Smith et al [1] demonstrated that small organic cations create a relatively rigid, nonpolar surface amenable to NOC uptake by adsorption, a surface characterized by a relatively high NOC uptake, isotherm nonlinearity, and competitive sorption.…”
Section: Introductionmentioning
confidence: 99%